Obsolete pesticide storage sites and their POP release into the environment--an Armenian case study - Dvorská, A; Sír, M; Honzajková, Z; Komprda, J; Cupr, P; Petrlík, J; Anakhasyan, E; Simonyan, L; Kubal, M (Environmental science and pollution research international, 2012)
Organochlorinated pesticides were widely applied in Armenia until the 1980s, like in all former Soviet Union republics. Subsequently, the problem of areas contaminated by organochlorinated pesticides emerged. Environmental, waste and food samples at one pesticide burial site (Nubarashen) and three former pesticide storage sites (Jrarat, Echmiadzin and Masis) were taken and analysed on the content of organochlorinated pesticides, polychlorinated dibenzo-p-dioxins and furans and dioxin-like polychlorinated biphenyls. Gradient sampling and diffusivity-based calculations provided information on the contamination release from the hot spots on a local scale. A risk analysis based on samples of locally produced food items characterised the impact of storage sites on the health of nearby residents. All four sites were found to be seriously contaminated. High pesticide levels and soil and air contamination gradients of several orders of magnitude were confirmed outside the fence of the Nubarashen burial site, confirming pesticide release. A storage in Jrarat, which was completely demolished in 1996 and contained numerous damaged bags with pure pesticides until 2011, was found to have polluted surrounding soils by wind dispersion of pesticide powders and air by significant evaporation of lindane and β-endosulfan during this period. Dichlorodiphenyltrichloroethane-contaminated eggs, sampled from hens roaming freely in the immediate surroundings of the Echmiadzin storage site, revealed a significant health risk for egg consumers above 1E-5. Although small in size and previously almost unknown to the public, storage sites like Echmiadzin, Masis and Jrarat were found to stock considerable amounts of obsolete pesticides and have a significant negative influence on the environment and human health. Multi-stakeholder cooperation proved to be successful in identifying such sites suspected to be significant sources of persistent organic pollutants.
Keywords: kur domácí; DDT; Animals; vejce; Armenia; hodnocení rizik; Chickens; Soil Pollutants; monitorování životního prostředí; Food Contamination; látky znečišťující půdu; znečištění životního prostředí; lidé; Risk Assessment; Environmental Pollution; Milk; kontaminace potravin; Air Pollutants; Endrin; Environmental Monitoring; Eggs; Pesticides; aldrin; Arménie; chlordan; zvířata; mléko; látky znečišťující vzduch; Chlordan; pesticidy; endrin; Aldrin; Humans